Laparotomy Exploration In Pediatric With Severe Thrombocytopenia: A Report - Arie Utariani; Rudy Vitraludyono (Faculty of Medicine-Universitas Airlangga, 2021)
Introduction: Perioperative bleeding in patients was a serious problem in the exploration of laparotomy, especially in severe thrombocytopenia patients. In addition, spontaneous bleeding often occurs in patients who have a platelet count of less than 10 to 20.109 cells. L-1 blood. When surgery must be performed on a patient with platelet counts < 50.109 cells L-1, platelet concentrate was urgently needed to be transfused during induction of anesthesia. Benefits and risks of transfusion before surgery had to be done on a per-patient basis. The available data was very limited in informing perioperative management of patients with thrombocytopenia. However, there have been previous reports of surgery cases in 66-year-old patients with a history of immune thrombocytopenia (ITP) and diagnosed with acute appendicitis related to disseminated intravascular coagulation (DIC), showing excellent postoperative hemostasis. Another one, a seven-year-old boy who has a severe refractory case of ITP with very low platelet counts was referred to urgent splenectomy performed without increase platelet counts before, and then the patient underwent plasma exchange (PE) after surgery. Those reports aimed to present 2 cases of laparotomy exploration in pediatric patients with severe thrombocytopenia. Case Report: The first laparotomy exploration was conducted on an 11-year-old boy who suffered acute perforated appendicitis. The patient obtained general anesthesia with intubation. The second laparotomy exploration was conducted on a 1-month-old baby boy with a weight of 3400 grams who suffered bowel low-level obstruction suspect Hirschsprung disease. The patient also obtained general anesthesia with intubation. Discussion The general anesthesia with oral intubation was successfully afforded to both patients for the laparotomy exploration with the preoperative condition under severe thrombocytopenia with receiving platelet transfusion therapy before surgery. Complications of spontaneous bleeding at the time of intubation were not found, no bleeding-difficult-intubation during surgery, and no symptoms of spontaneous bleeding were found. Postoperatively, platelet levels gradually improved. Conclusion: Exploration of laparotomy in patients with severe thrombocytopenia can be carried out with the support of platelet transfusion and providing general anesthesia with oral intubation to patients.